The essential language needs to develop the performance of female Arabic language teachers in light of the Professional Licensing Standards document for teachers in Saudi Arabia from the viewpoint of teachers and supervisor in Madinah - Alharbi, Ashwaq Abdullah Fahad; Haji, Khdijah Mohamad Omar (Journal of Educational and Psychological Sciences, 2021)
The study aimed at identifying the essential language needs to develop the performance of female Arabic language teachers in light of the document Standards for Professional Licensing for teachers in Saudi Arabia from the viewpoint of teachers and supervisors in Madinah. To achieve this, we have followed a descriptive survey approach where we designed a questionnaire to determine the language needs of female Arabic language teachers. The questionnaire was applied to a sample of female Arabic language teachers and supervisors in the Medina area, Their number reached (756), including (735) female teachers and (21) supervisors, using statistical software (SPSS). The results of the survey demonstrated (73) essential language need to develop the performance of female Arabic language teachers, distributed in the two fields: language skills and linguistics. The results showed also that the overall degree of the language needs I got an overall average (4.15 out of 5), i.e. with a (high) degree, and at the level of the two main areas; (The domain of language skills) got an average of (4.30) with a degree (very large), and it came in first place (the axis of speaking and reading in a correct and sound language, with an average of (4.42), followed by (the axis of proper written expression and taking into account correct spelling with an average of (4.25), then It is followed by (the axis of comprehension of the audio and reading text, with an average of (4.24), all of which are in degrees (very large), while (the field of linguistic sciences skills) got an arithmetic average of (4) with a degree (large), while the axes of the field came in first place, the axis (Grammar). And morphology) with an average of (4.36), to a degree (very large), followed by the (Literature) axis with an average of (3.99), then the (Rhetoric and Criticism) axis with an average of 3.98, then the (Linguistics) axis with an average of 3.96, and came in the last rank (The performances and rhyme averaged (369), all with a degree of appreciation (high). and there were no statistically significant differences between the female teachers ’and supervisors’ views on those needs. Also, there are no statistically significant differences between the responses of female Arabic language teachers concerning language needs due to two variables: years of experience, and the educational level in all units, except for the comprehension of the audio and readable text unit that is attributed to the variable of years of experience in favor of experienced teachers (from 5-10) years. While the comprehension of the audible and read text, and literature units were attributed to the variable of the educational level in favor of female secondary school teachers. Based on the results, the researchers recommended programs for training female Arabic language teachers and designing professional development programs in line with language needs, and engaging female Arabic language teachers in determining the language needs necessary to develop their professional performance in a way that enables them to perform their future roles with high efficiency.